The Influence of Literacy-Based Learning Strategies on Students’ Critical Thinking Skills at SMA Muhammadiyah 01 Medan - Syahputra, Arif; Aulia, Zanzabila; Hidayat, M. Reza (Integrasi: Jurnal Studi Islam dan Humaniora, 2025)
This study aims to examine the influence of literacy-based learning strategies on students’ critical thinking skills at SMA Muhammadiyah 01 Medan. A quantitative approach with a quasi-experimental design was employed. The population consisted of all eleventh-grade students, and the sample was selected purposively. Data were collected through critical thinking tests administered before and after the implementation of the treatment. The data analysis revealed a significant improvement in students' critical thinking skills following the application of the literacy-based learning strategy. These findings indicate that literacy-based learning strategies are effective in fostering students’ critical thinking by encouraging deep reading, analytical thinking, and the development of logical and reflective arguments.